2016
DOI: 10.4172/2161-0525.1000358
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Doped Titania for Photocatalytic Degradation of Dyes in Visible Light

Abstract: J o u rn al of En v ir o n m en tal & A n a ly ti c al Toxico lo g y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Among the most prominent phases of TiO2 namely Anatase, rutile and Boookite, the first two phases are most studied systems as seen from the data given in Table.1. The position of oxygen ions on the anatase surface is in a triangular arrangement which allows significant absorption of organic molecules, whereas, the orientation of titanium ions in the anatase phase creates a favourable reaction condition with the absorbed organic pollutants [17][18][19][20][21][22][23][24]. Interestingly, these favourable structural arrangements of oxygen and titanium ions are not present in the rutile phase.…”
Section: The Literature So Farmentioning
confidence: 99%
“…Among the most prominent phases of TiO2 namely Anatase, rutile and Boookite, the first two phases are most studied systems as seen from the data given in Table.1. The position of oxygen ions on the anatase surface is in a triangular arrangement which allows significant absorption of organic molecules, whereas, the orientation of titanium ions in the anatase phase creates a favourable reaction condition with the absorbed organic pollutants [17][18][19][20][21][22][23][24]. Interestingly, these favourable structural arrangements of oxygen and titanium ions are not present in the rutile phase.…”
Section: The Literature So Farmentioning
confidence: 99%
“…According to them the samples composed of agglomerates larger than pure titania should be considered for better catalytic behavior [65]. AVASARALA et al in the same way found fine crystals aggregated to form irregular shaped particles of magnesium doped titania catalyst with average size of 1.04 µm range [31]. CIFCI observed silver doped titania particles having different shapes of grains with irregular boundaries and many smaller crystals combined to form aggregates [66].…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Similarly, nanotitania modified food packaging films have been developed to produce antimicrobial and photocatalytic food packaging with toxin passivation in order to preserve food safely [22]. Other titania base nanomaterials with enhanced photocatalytic and antibacterial activities have also been developed by the previous scientists for example, doped titania nanorods, silica/titania nanospheres, silver doped titania sol-gel films, Ag doped TiO 2 -chitosan (STC) prepared by the inverse emulsion cross-linking reaction, Ag-TiO 2 composite nanofilms on silicon wafer synthesized by sol-gel spin-coating technique, Cu-doped titanium dioxide thin films on glass substrate, sulfur-doped titania thin films prepared by atmospheric pressure chemical vapour deposition, silver-nanostructures coated TiO 2 thin films on pure titania, carbon-doped TiO 2 and nitrogen-doped TiO 2 substrates using thermal reduction method, TiO 2 (N)/Ag/TiO 2 (N) sandwich films containing silver embedded between two TiO 2 (N) layers [23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 represents low photocatalytic activity due to its wide band gap, high electron-hole pair recombination rate and also its excitation only under UV light wavelength (Benjume et al 2012). Various approaches have been practiced to retard its charge recombining deficiency such as depositing noble metals like Pt or Pd on TiO 2 surface , doping other metal such as magnesium on TiO 2 surface (Avasarala et al 2016) and combining TiO 2 with other metal oxides such as ZrO 2 to form nanoconjugates (Benjume et al 2012). Nanoconjugates also called mixed oxide composites have more efficient photocatalytic activity than pure substances through the generation of new active sites, thermal stability, improved mechanical strength and surface area of titania.…”
Section: Introductionmentioning
confidence: 99%